The sensory world: An introducction to sensation and perception - Bennett, Thomas (California: Brooks/Colepublishing Company, 1978)
I:Introduction. II. Measuring the sensory experience. III. Vision. VI. Audition. V. The other senses: Taste, olfaction, and Somesthesis.
Keywords: Percepción Sensorial